First-Principles Studies of Hydrogen Adsorption at Pd-SiO(2) Interfaces - Irokawa, Yoshihiro (Sensors (Basel), 2015)
The interaction of hydrogen with Pd-SiO(2) interfaces has been investigated for the first time using first-principles calculations based on density functional theory. The hydrogen-induced polarization at the Pd-SiO(2) interfaces was evaluated using Pd-SiO(2) interface supercells. As a result, the potential change induced by interfacial hydrogen atoms was not observed even for hydrogen concentration of ~1.3 × 10(15) cm(−2) at the Pd-SiO(2) interface. This result implies that hydrogen does not create an electric double layer at the Pd-SiO(2) interface but change the property of the SiO(2) region, resulting in the hydrogen sensitivity of the devices.